An exploration of theoretical concepts and methods for assessing risk impacts on the variability between design stage elemental cost plan and tender sum - Adafin, J; Wilkinson, S; Rotimi, JOB; Odeyinka, H (Commission of the International Council for Research and Innovation in Building and Construction, 2014)
Reliable prediction of final tender sums of building projects from the cost plan has posed challenges for construction industry practitioners in New Zealand, especially Quantity Surveyors. No matter how much care and effort is put into the preparation of design stage elemental cost plans, significant deviations are usually observed between these cost plans and the final tender sum. The major reason for this deviation is the risk inherent in both design and construction. This study is a literature-based theoretical exploration and part of an on-going doctoral research aimed at assessing the impacts of risk on the variability between design stage elemental cost plan and final tender sum. This paper first provides a review of the risk elements inherent in preparing the design stage elemental cost plan by demonstrating the theoretical context. Also, it develops a methodology for assessing risk impacts on the variability between the design stage elements cost plan and final tender sum. The insights gained from the foregoing steps then helped in devising theoretical concepts for securing the design stage elemental cost plan as a reliable budgetary tool that guarantees cost certainty for building projects, and also a methodological frame-work for assessing the variability between the design stage elemental cost plan and final tender sum.
Keywords: Elemental cost plan; Exploration; Final tender sum; Risk; Variability